The Co-inhibitor BTLA Is Functional in ANCA-Associated Vasculitis and Suppresses Th17 Cells - Werner, Kai; Dolff, Sebastian; Dai, Yang; Ma, Xin; Brinkhoff, Alexandra; Korth, Johannes; Gäckler, Anja; Rohn, Hana; Sun, Ming; Cohen Tervaert, Jan Willem; van Paassen, Pieter; Kribben, Andreas; et al. (Frontiers in Immunology, 2019)
Objectives: The activation and inhibition of T-cells has been well studied under physiological conditions. Co-inhibition is an important mechanism to keep effector T-cells in check. Co-inhibitors mediate peripheral self-tolerance and limit the immune response. Dysfunctional co-inhibition is associated with loss of T-cell regulation and induction of autoimmunity. Therefore, we investigated the co-inhibitor B- and T-Lymphocyte attenuator (BTLA) in ANCA-associated vasculitis (AAV). Methods: 56 AAV patients and 32 healthy controls (HC) were recruited. Flow cytometry was performed to investigate the expression of BTLA on T-cells. Double negative T-cells were defined as CD3+CD4-CD8-. To assess the functionality of BTLA, CFSE-labelled T-cells were stimulated in presence or absence of an agonistic anti-BTLA antibody. In addition, impact of BTLA-mediated co-inhibition on Th17 cells was studied. Results: AAV patients in remission had a decreased expression of BTLA on double negative T-cells (CD3+CD4-CD8-). On all other subtypes of T-cells, expression of BTLA was comparable to healthy controls. TCR-independent stimulation of T-cells resulted in down-regulation of BTLA on Th cells in AAV and HC, being significantly lower in HC. Co-inhibition via BTLA led to suppression of T-cell proliferation in AAV as well as in HC. As a result of BTLA mediated co-inhibition, Th17 cells were suppressed to the same extent in AAV and HC. Conclusion: BTLA expression is altered on double negative T-cells but not on other T-cell subsets in AAV. BTLA-induced co-inhibition has the capacity to suppress Th17 cells and is functional in AAV. Thus, BTLA-mediated co-inhibition might be exploited for future targeted therapies in AAV.